Functional connectivity of the striatum in experts of stenography. Issue 5 (25th March 2015) - Ito, Takehito; Matsuda, Tetsuya; Shimojo, Shinsuke
Abstract Introduction Stenography, or shorthand, is a unique set of skills that involves intensive training which is nearly life‐long and orchestrating various brain functional modules, including auditory, linguistic, cognitive, mnemonic, and motor. Stenography provides cognitive neuroscientists with a unique opportunity to investigate the neural mechanisms underlying the neural plasticity that enables such a high degree of expertise. However, shorthand is quickly being replaced with voice recognition technology. We took this nearly final opportunity to scan the brains of the last alive shorthand experts of the Japanese language. Methods Thirteen right‐handed stenographers and fourteen right‐handed controls participated in the functional magnetic resonance imaging (fMRI) study. Results The fMRI data revealed plastic reorganization of the neural circuits around the putamen. The acquisition of expert skills was accompanied by structural and functional changes in the area. The posterior putamen is known as the execution center of acquired sensorimotor skills. Compared to nonexperts, the posterior putamen in stenographers had high covariation with the cerebellum and midbrain.The stenographers' brain developed different neural circuits from those of the nonexpert brain. Conclusions The current data illustrate the vigorous plasticity in the putamen and in its connectivity to other relevant areas in the expert brain. This is a case of vigorous neural plastic reorganization in response to massive overtraining, which is rare especially considering that it occurred in adulthood.